Toxicity Test of the Combination of N-Hexane Extract of Black Pepper (Piper nigrum L.) and Yogurt on the Digestive Organs of Mice (Mus musculus) - Inayah, Nurul; Mutiati, Enni; Sa’diyah, Halimatus (Electronic Journal of Education, Social Economics and Technology, 2024)
Black pepper (Piper nigrum L) is a spice that is widely used in cooking by people in Indonesia, earning the nickname "King of Spice". The chemical content in Black Pepper (Piper nigrum L) is piperine. Piperine can activate Transient Receptor Potential Vanilloid Type 1 (TRPV1), causing heartburn, heat and increased stomach acid. Therefore, researchers combined black pepper (Piper ningrum L.) with yogurt, because it is known that yogurt can suppress stomach acid and the growth of bad bacteria in the intestines. The aim of this research was to determine the potential toxicity of the combination of black pepper extract (Piper ningrum L.) and yogurt on the digestive organs and the duration of death of mice (Mus musculus). In research that has been carried out using RAL with 5 treatments and 4 replications. The samples used were female mice (Mus musculus). Next, descriptive analysis was carried out. The results of the research that has been carried out show that the concentration of 25 mg/kg bw in the combination of Black Pepper (Piper ningrum L.) extract and yogurt on the anatomy of the stomach and intestines is closer to the positive control (P1) and the combination of Black Pepper (Piper ningrum L.) extract and yogurt with a concentration of 75 mg/kg bw on stomach and intestinal anatomy was closer to the negative control (P0).